PRINSIP PRODUK PERBANKAN SYARIAH - Afif, Nurullah Sururi (www.bsi.ac.id, 2009)
Abstract:Basically syariah's bank take islam principle as referenced as deep going its effort. In does transactions, be not been let marks sense elements that contain something that is prohibitted. syariah's principles that is utilized in syariah's bank amongst those is Murabahah, Ijarah, Istishna, Regards, Sharf, Mudharabah, Partnership, wadiah, Rahn, Qardh, Wakalah, Kafalah, HiwalahKeyword:Islamic Banking, Islamic Principles